Linear motion control with a low-power hydraulic switching converter - Part I: Concept, test rig, simulations. (September 2015) - Kogler, Helmut; Scheidl, Rudolf
Switching control can be employed for hydraulic motion control. Among the many hydraulic switching methods investigated so far, the so-called hydraulic buck converter convinces by its simplicity. It consists of two switching valves, an inertance pipe, and a hydraulic accumulator to flatten the pulsation resulting from switching. This accumulator entails significant softness and nonlinearity which, in combination with sealing friction of the hydraulic cylinder, may lead to inferior performance with simple control concepts. In this paper a sub-kilowatt hydraulic buck converter, its components, design, dimensioning, and steady-state performance characteristics are presented first. Measurements on a testrig for linear motion employing a simple P-controller show the necessity of a model-based control to achieve the desired control performance. Therefore, a dynamic model of the converter and the linear drive is derived and studied by simulations. It is shown that the model incorporates the relevant physical effects and that it is qualified for a flatness-based control, which is derived in Part II of the publication.